EXCHANGE RATE POLICY - Plačkov, Slađana G; Pivašević, Jelena; Vojnović, Jelena (International Journal of Economic Practice and Policy, 2013)
Small oscillations of exchange rate certainly affect the loss of confidence in the currency (Serbian dinar, CSD) and because of the shallow market even the smallest change in the supply and demand leads to a shift in exchange rate and brings uncertainty. Some economists suggest that the course should be linked to inflation and thus ensure predictable and stable exchange rates. Real exchange rate or slightly depressed exchange rate will encourage the competitiveness of exporters and perhaps ensure the development of new production lines which, in terms of overvalued exchange rate, had no economic justification. Fixed exchange rate will bring lower interest rates, lower risk and lower business uncertainty (uncertainty avoidance), but Serbia will also reduce foreign exchange reserves by following this trend. On the other hand, a completely free exchange rate, would lead to a (real) fall of Serbian currency, which in a certain period would lead to a significant increase in exports, but the consequences for businessmen and citizens with loans pegged to the euro exchange rate, would be disastrous. We will pay special attention to the depreciation of the exchange rate, as it is generally favorable to the export competitiveness of Serbia and, on the other hand, it leads to an increase in debt servicing costs of the government as well as of the private sector. Oscillations of the dinar exchange rate, appreciation and depreciation, sometimes have disastrous consequences on the economy, investors, imports and exports. In subsequent work, we will observe the movement of the dinar exchange rate in Serbia, in the time interval 2009-2012, in order to strike a balance and maintain economic equilibrium. A movement of foreign currencies against the local currency is controlled in the foreign exchange market, so in case economic interests require, The National Bank of Serbia (NBS), on the basis of arbitrary criteria, can intervene in the market.
Keywords: EXCHANGE RATE; EXCHANGE RATE POLICY; appreciation; depreciation; The National Bank of Serbia (NBS)